May Sinclair’s and H. G. Wells’s Involvement in the Suffrage Movement - Pudelko, Brygida (Journal of History Culture and Art Research, 2015)
May Sinclair’s and H. G. Wells’s Involvement in the Suffrage Movement Abstract For May Sinclair the Woman Suffrage Movement was an idea that shaped her life, or at least the culture that produced her. Sinclair was actively involved and a vocal supporter of the suffrage movement. Not a militant herself, she was a member of the Women’s Freedom League for a year. She was also a member of the Women Writers Suffrage League (WWSL). In 1912 she became one of twelve vice-presidents of the WWSL. Sinclair was also not averse to writing statements for publication in Votes for Women. But despite her involvement in the suffragette movement in the years leading up to 1914, Sinclair was not comfortable with the aggressive militant side of it. H. G. Wells was among the considerable number of male writers of the day who openly supported the feminist cause and wrote for women’s magazines. Wells supported the demand for the vote, but seeing that more than access to parliamentary democracy would be required if women were really to be free, he had no patience with the limited perspectives of Emmeline and Christabel Pankhurst and their movement. Wells’s assessment of his own position would seem to prove that he did not intend to make fun of the suffragettes nor of the many other feminists who did not see the wider connections of their movement. Like Sinclair he did not support the militant suffragettes. Rather he despaired of their capacity to accomplish the task they had set themselves. Knowing that feminism was coming into maturity, he had actively supported the campaign for financial and political independence for women.